Follow the leader - Ford, Miela (New York : Greenwillow Books, 1996)
Two polar bears in the zoo play follow-the-leader.
1.3
K-3
K-3
School Library Journal
Library Talk
Keywords: Polar bear -- Fiction; Bears -- Fiction; Polar bear -- Fiction; Bears -- Fiction